Role of the CX3CL1/CX3CR1 axis in iron metabolism and immune regulation during acute Trypanosoma cruzi infection - Pio, Sirlaine; Menezes, Tatiana Prata; Louise, Vitória; Costa, Guilherme de Paula; Oliveira, Daniel Malta; Carlos, Natiele; Paula-Gomes, Silvia; Perucci, Luiza Oliveira; Talvani, André (Frontiers in Immunology, 2025)
IntroductionDuring Trypanosoma cruzi infection, the immune system activates a robust inflammatory response, involving cytokines and chemokines like IFN-γ, TNF, IL-6, IL-1β, CCL2, and CCL5, to control parasite replication. The CX3CL1 chemokine and its receptor, CX3CR1, have been implicated in amplifying inflammation through pathways like NF-κB, MAPKs, STATs, TLRs, and NLRs, contributing to tissue damage. This study evaluated the effects of blocking CX3CR1 with the allosteric antagonist AZD8797 in a murine model of acute T. cruzi infection. MethodsMale C57BL/6 mice were infected with 103 trypomastigote forms of T. cruzi (Y strain) and received AZD8797 (10 mg/kg) intraperitoneally for 10 days. On the 10th day, animals were euthanized and heart, skeletal muscle, and liver tissues were collected for CX3C L1 protein expression, biomarkers (IL-1β, IL-4, IL-6, IL-10, IL-15, IL-17, IFN-γ, TNF, and CCL2) quantified by Cytometric Bead Array and Enzyme Immunoassay. ResultsTreatment reduced spleen mass and cardiac levels of CCL2 and IL-15, with an increase of IL-4. Conversely, in skeletal muscle, TNF, IL-6, and IL-10 increased, while IL-15 decreased. Liver tissue showed reduced IL-15, IL-6, and IL-1β levels, alongside lowered plasma hepcidin and ferritin concentrations. DiscussionThese findings highlight CX3CL1’s site-specific role in modulating inflammation and iron metabolism during acute T. cruzi infection, suggesting its potential as a therapeutic target for infection management and disease prognosis.